Exploring Picture Series, Students Motivation and Gender Toward Speaking Achievement - Kurnia Saputri; Darmawan Budiyanto; Sisca Meidina Saputri; Enny Hidajati; Maryanti Sawitry (Journal of English Education and Teaching, 2023)
The media utilized in the teaching and learning process should adapt to the circumstances and settings, as well as be compatible with the abilities of the students. The media industry has a common need for creative men and women who can effectively communicate information and ideas via words and visuals. This study was aimed to found out: whether or not there were an influence of interaction among picture series, motivation and gender toward speaking achievement. Method of this research used quantitative with factorial 2x2x2 design approach. There were 60 students as sample, 30 students for experimental group and 30 students for control group. The sample was taken by using purposive sampling., the data were collected by using speaking test and questionnaires. To verify the hypotheses, the data were analyzed by using three-way ANAVA. Based on the data analysis, the result of three-way ANAVA showed that the interaction between: 1) the experiment and control classes obtained significant values = 0.001 < 0.05, the first hypothesis was acceptable, 2) the male and female genders obtained significant values = 0.367 > 0.05, the second hypothesis cannot be accepted, 3) high and low motivation obtained significant value = 0.085 > 0.05, the third hypothesis is unacceptable, 4) class and gender obtained significant value = 0.820 > 0.05, the fourth hypothesis is not acceptable, 5) class and motivation obtained Significant value = 0.669 > 0.05, then the fifth hypothesis is unacceptable, 6) Gender and motivation obtained Significant value = 0.015 < 0.05, then the sixth hypothesis is acceptable, and 7) the interaction among class, gender and motivation was obtained Significant value = 0.380 > 0.05, the seventh hypothesis was unacceptable. Thus, it could be concluded that there was no interaction between class, gender and motivation for speaking achievement scores.